SISTEM INFORMASI ADMINISTRASI UJIAN MENGGUNAKAN FRAMEWORK CODEIGNITER 4.0 DAN DATABASE MySQL DI FAKULTAS TEKNIK UKWK - Gilang Wahyu Susanto; Fransiskus Xaverius Agung Perkasa Jampur; Fery Satria Kristianto (Journal of Information System and E-business, 2023)
Implementation of learning support administrative activities at the Widya Karya Malang Unika Faculty of Engineering, one of which is registration for exams, both Field Work Practices or internships as well as Thesis or Final Assignments which are carried out routinely, has constraints, namely manual operations that are repeated in data input or printing form requirements, this is due to this operational activity has not been systemized. In the analysis and observations that the authors did, the authors encouraged the authors to design and build an exam administration information system that could help the operational activities of exam administration in an integrated, website-based manner, making it easier for related users to access data. This research produced an exam administration information system with student users, supervisors and examiners, Ka. study program, and faculty administration staff where the output of the system provides features for student registration for exams, the process of guidance and validation of exam readiness, making exam schedules, printing administration forms easily, and providing assessment of exam results, so that they can help the performance of the exam administration process at the Widya Catholic University Faculty of Engineering Malang work.